Effect of limited near-wall inlet data on the direct numerical simulation of turbulent channel flow. (April 2020) - Ezhilsabareesh, K.; Atkinson, Callum; Lozano-Duran, Adrian; Schimd, Peter J.; Jimenez, Javier; Soria, Julio
Abstract: Direct numerical simulation (DNS) of turbulent flows require a large computational domain and a long simulation time to capture and evolve the large-scale structures and attain a statistically stationary state. In contrast, experimental measurements can relatively easily capture the large-scale structures, but struggle to resolve the dissipative flow scales. This study investigates the spatial extent required for the DNS of a turbulent channel flow to recover turbulent fluctuations and energy when using experimental inlet data which is typically unable to capture fluctuations down to the viscous sub-layer. Synthetic experimental fields from streamwise periodic channel flow DNS at Reτ = 180 are used as an inlet for a channel flow DNS with inlet-outlet boundary conditions. The effect of limited near-wall data at the inlet is examined by removing the near-wall energy and fluctuations in all but the zeroth Fourier mode. The influence of limited near-wall data on the convergence of mean and streamwise fluctuating velocity profiles is less significant when the fluctuations are removed at the inlet up to y + = 5. However, the spanwise fluctuations are slightly weakened. The spanwise energy spectra suggest that at 1/16 of the domain length (x/h ≍ π/4) the flow scales are recovered. When the fluctuations are removed up to y + = 17 or greater, recovery of full range of flow scales requires a domain larger than x/h = 4π.